Does family ownership moderate the relationship between board gender and capital structure of Saudi-listed firms? - Mohammed Naif Alshareef (Cogent Business & Management, 2024)
This article examines how family ownership may influence the nexus between board gender and capital structure. The research data was gathered from the listed companies on the Saudi exchange market from 2013 to 2022 and analysed using the fixed effects framework. More importantly, additional analysis was provided using the generalised method of moments approach. The research findings suggest that board gender exerts an insignificant positive effect on capital structure. The moderation result shows that as family ownership rises, the effect of board gender on leverage may decrease. Thus, these findings remain consistent using diverse capital structure proxies. This outcome implies that gender diversity does not seem to be an important determinant of debt supply in Saudi Arabia. Perhaps, due to the countries unique institutional structure and culture. The result contradicts agency and resource dependency views, which emphasise that gender diversity may enhance firms' strategic choices and facilitate more access to debt capital. Conversely, the moderation analysis implies that family ownership may substitute the stringent monitoring and resource provision role of the board gender. The policy implication of this finding is that family ownership seems to be an important mechanism that may strengthen firms' internal governance and boost creditors' confidence.
Keywords: 650; Board gender; capital structure; leverage; family ownership; moderation analysis; saudi listed companies